Effects of Finaplix® Synovex-S®, and Ralgro® implants, singularly or in combinations, on performance, carcass traits, and longissimus palatability of Holstein steers - J.K. Apple; D.D. Simms; Gerry L. Kuhl; Michael E. Dikeman; Curtis L. Kastner (Kansas Agricultural Experiment Station Research Reports, 1990)
Over the entire feeding period (249 d). Finaplix® (F) plus Synovex-S® (S)-implanted steers had higher (P.05) among treatments. only 50% of F+S carcasses graded low Choice or higher compared to a range of 75 to 100% for the other treatments. The only meat palatability differences were tenderness scores; steaks from Sand F + R steers were less tender (P<.07) than those from Rand C steers.
Keywords: Cattlemen' s Day; 1990; Kansas Agricultural Experiment Station contribution; no. 90-361-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 592; Beef; Holsteins; Implants; Performance; Carcass traits; Meat palatability